2013
DOI: 10.9790/0853-0656166
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intestinal Helminthic Infection among School Children in Rural and Semi Urban Communities in Nigeria.

Abstract: The present

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…On the other hand, the present study showed very much higher prevalence of intestinal parasitic infections compared to the study conducted in Yadot primary school children of South Eastern Ethiopia 26.2% [12] and Dera district, South Gonder 20.9% [19]. Other studies conducted in many developing countries also agree with the current study that the prevalence of soil transmitted parasites is still high compared to WHO recommending and guideline [4, 11, 14, 16].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…On the other hand, the present study showed very much higher prevalence of intestinal parasitic infections compared to the study conducted in Yadot primary school children of South Eastern Ethiopia 26.2% [12] and Dera district, South Gonder 20.9% [19]. Other studies conducted in many developing countries also agree with the current study that the prevalence of soil transmitted parasites is still high compared to WHO recommending and guideline [4, 11, 14, 16].…”
Section: Discussionsupporting
confidence: 87%
“…This study argues that the prevalence of intestinal protozoan infections was ranging from 2.0–7.0% in developed countries and 20.0 – 30.0% in most developing countries [15]. Another study done in Nigeria and Tanzania confirmed that intestinal protozoa are a public health problem [16, 20]. Indeed, studies done in Ethiopia showed that almost all under-five children were infected with at least one of the two pathogenic intestinal protozoa [13, 12, 19].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations